Peripheral T cell lymphoma not otherwise specified (PTCL-NOS) presenting as an endobronchial lesion: Case report and literature review. (2018) - Sueyasu, Takuto; Tobino, Kazunori; Okahisa, Masanobu; Murakami, Kojin; Goto, Yuki; Munechika, Miyuki; Yoshimine, Kohei; Nishizawa, Saori; Ko, Yuki; Yoshimatsu, Yuki; Asaji, Mina; Tsuruno, Kosuke; et al.
Abstract: Peripheral T cell lymphoma not otherwise specified (PTCL-NOS) is a rare entity of lymphoma. We herein report an even rarer case of a 68-year-old male with PTCL-NOS presenting as an endobronchial lesion, and review previously published cases in the literature. Initially, he was referred to our hospital for further investigation of the right upper lobe consolidation on chest radiograph. Computed tomography and 18F-fludeoxyglucose positron emission tomography revealed a right hilar mass with obstruction of the main bronchus and submandibular, right axillary and mediastinal lymphadenopathy. Pathological examination of the biopsy specimens from of the endobronchial lesion and subcutaneous nodule revealed PTCL-NOS. Chemotherapy was started but he finally died due to septic shock after the second-line chemotherapy.